Efeitos de uma intervenção analítico-comportamental em familiares de portadores do Transtorno Obsessivo-Compulsivo sobre a acomodação familiar - Andrade, Lilian Regina Boarati de (2015)
Participation in rituals is often observed in relatives of Obsessive-Compulsive Disorder (OCD) patients. Family members change their routine, contributing to the maintenance and the strengthening of ritualistic responses. This participation has been called Family Accomodation. According to the perspective of Behavior Analysis, both the behaviors of OCD patients as of their relatives are controlled by environmental variables. This study aimed to evaluate a family-directed intervention procedure in order to reduce family accommodation. The subjects were three dyads of adults patients with OCD and their mothers. Before the intervention procedure, interviews were performed separately with the two participants from each dyad, in order to screening the patients´ rituals and the mothers´ accommodation responses. Then, weekly meetings were held between the researcher and the mothers for 12 to 14 weeks. Mothers were instructed to record the daily rituals demanding their participation and if they had adhered to them or not. These records allowed the researcher to establish an order of family accommodation responses according to their frequency, from the lowest to the highest ones. After explaining to mothers how their behavior could be maintaining the ritualistic responses of their offsprings, the researcher instructed them not participate in rituals (Extinction) that occurred less often (supposedly easier eliminating) and to differentially reinforce any other class of responses (DRO). During the intervention, at each meeting, the researcher analyzed the records brought by mothers and if she realized that mothers had followed the instructions to extinguish the rituals and reinforce their offsprings´other responses, she provided them with praise. Once one class of accommodation responses was eliminated (measured by daily records of mothers), the researcher instructed the mothers to extinguish the next ritual following the order from low to high frequency. In weekly meetings, the researcher could also review with mothers the main difficulties faced in extinguishing the accommodation responses and provide guidance on how to act in everyday situations. The analysis of the agreement conducted in 30% of records between the researcher and an independent evaluator indicated a general agreement of 90.57%. The results showed that although the ritualistic and the accommodation responses presented by the three dyads were very different, mothers succeeded to eliminate most of their accommodation responses. At the xvii same time, there was also noted a reduction in requests from the OCD patients directed their mothers to take part of their rituals. An assessment carried out 21 days after the end of the intervention (follow-up) showed that two of the three mothers kept the complete elimination of their accommodation responses addressed in the intervention. The third mother presented the complete elimination of two classes of accommodation responses, decreased the average frequency of one class of accommodation responses and maintained the frequency of another class as that presented at the last week of the intervention. It was concluded that family accommodation can be changed by providing information on its role in maintaining the ritualistic responses of OCD patients associated with instructions for family to extinguish the rituals and by social reinforcement of family behavior change